Renal impairment in a rural African antiretroviral programme - Franey, Cara; Bärnighausen, Till; Newell, Marie-Louise (BMC infectious diseases, 2009)
There is little knowledge regarding the prevalence and nature of renal impairment in African populations initiating antiretroviral treatment, nor evidence to inform the most cost effective methods of screening for renal impairment. With the increasing availability of the potentially nephrotixic drug, tenofovir, such information is important for the planning of antiretroviral programmes